The Wellbeing of Italian Peacekeeper Military: Psychological Resources, Quality of Life and Internalizing Symptoms - Loscalzo, Yura; Giannini, Marco; Gori, Alessio; Fabio, Annamaria Di (Frontiers in Psychology, 2018)
Working as a peacekeeper is associated with the exposure to acute and/or catastrophic events and chronic stressors. Hence, the meager literature about peacekeepers’ wellbeing has mainly analyzed Post-Traumatic Stress Disorder (PTSD). This study aims to deep the analysis of the wellbeing of peacekeepers military. Based on the few studies on this population, we hypothesized that Italian peacekeeper military officers and enlisted men (n = 167; 103 males, 6 females, 58 missing) exhibit lower levels of internalizing symptoms (i.e., PTSD, depression, general anxiety, obsessions, and somatization) as compared to a control group (n = 60; 32 males, 28 females). Moreover, we hypothesized that peacekeepers have higher levels of psychological resources (i.e., self-efficacy, self-esteem, social support) and quality of life (i.e., higher life satisfaction and lower general stress). We compared the groups by means of MANOVAs on the subscales of the Psychological Treatment Inventory (PTI; Gori et al., 2015). We found that Italian peacekeepers have lower internalizing symptoms and higher levels of self-efficacy and self-esteem than the control group; however, no statistically significant differences were observed on perceived social support. :. Finally, peacekeepers have a higher quality of life: scores reflect higher life satisfaction and lower distress than the control group. This study is in line with previous literature supporting the claim that Italian peacekeeper military officers have sufficient psychological resources for coping with the stressful situations implied in peacekeeping missions. Future studies should deepen the analysis of the military’s psychological characteristics by comparing war veterans and peacekeeper military.